Effects of Yoga-Based Intervention with Bhramari Pranayama and Chakra Meditation on Sympatho-Vagal Balance in Perimenopausal Women: A Randomized Controlled Trial - Jayachitra Subramanian; Subbulakshmi Velusamy; Ethiraj Balaji; Nirmal Michael Salvi; Erianti (Physical Rehabilitation and Recreational Health Technologies, 2026)
Purpose. Perimenopause is associated with progressive altered autonomic regulation manifesting as sympathetic hyperactivation and impaired parasympathetic modulation, increasing cardiovascular and psychological vulnerability. Heart rate variability (HRV) provides a validated, non-invasive index of cardiac autonomic regulation. Yoga-based interventions incorporating controlled breathing and meditation may favorably modulate sympatho-vagal balance, yet robust randomized controlled trial (RCT) evidence in perimenopausal women specifically examining assessment of selected HRV indices is lacking. Objective: to evaluate the effect of an eight-week structured yoga intervention combining Bhramari pranayama and chakra meditation on HRV time-domain parameters (RMSSD, pNN50, heart rate) and frequency-domain parameters (LF power, HF power, LF/HF ratio) in peri-menopausal women. Materials & Methods. Parallel-group, single-blind RCT. Sixty perimenopausal women (40–55 years) were randomized (1:1) to a yoga intervention group (n=30) or a waitlist-control group (n=30). The yoga group received 60-minute supervised sessions five days/week for eight weeks, incorporating Bhramari pranayama (20 min) and chakra meditation (20 min). Short-term HRV (5 min, supine) was recorded using a validated ECG-based system and analyzed per Task Force (ESC/NASPE 1996) standards. Primary outcomes: RMSSD, pNN50, LF/HF ratio. Secondary outcomes: heart rate, systolic blood pressure, LF power, HF power. Between-group changes were compared by ANCOVA (baseline-adjusted). Effect size: Cohen's d. Results. Fifty-six participants completed the trial (28 per group; retention: 93.3%). Yoga group demonstrated significant post-intervention improvements vs. controls: RMSSD (34.7±7.1 vs. 23.4±6.0 ms; Δ=+12.3 ms, 95%CI: 9.1–14.5, p